The psychological impact of COVID-19 and the subsequent social isolation on the general population of Karnataka, India (Journal of Ideas in Health, 2020)
Background: The COVID-19 pandemic has various unfavorable effects on individuals and the community. This study aims to assess the psychological impact of the COVID-19 epidemic and the subsequent social isolation on the general population of Karnataka, India. Methods: A web-based cross-sectional survey was conducted in Karnataka from 8 to 14 April 2020 using the snowball technique. The psychological impact was assessed with the help of the nine-item Patient Health Questionnaire-9 (PHQ-9) and seven-item General Anxiety Disorder-7 (GAD-7) questionnaires. IBM SPSS Statistics Subscription version 16.0 was recruited to analyze the data. Descriptive (Mean + Standard Deviation) and bivariate (Pearson chi-square and ANOVA tests) analysis used to present data with the significance level set at less than 0.05.Results:  This study included 1537 participants from 26 cities in Karnataka. About two-thirds of the respondents were undergraduate students (951, 61.9%), females (768, 50.0%), and 40.1% stayed about 15-20 days in social isolation. The prevalence of depression was 47.0%, and anxiety was 41.5%, respectively, among the surveyed sample. After the analysis, the age group 21-30 year old (P < 0.001), females P < 0.001), urban residents (P = 0.021), and the students (P p < 0.001) were significant for depression. However, only the age group 31-40 years was found to be more susceptible to anxiety.Conclusion: As important as addressing the psychological effects, knowing people at risk of developing mental illnesses will contribute effectively to providing appropriate psychological rehabilitation programs at the right time. References• World Health Organization, Novel Coronavirus (2019-nCoV) Situation Report –1, 21 January 2020. Available from: https://www.who.int/docs/default-source/coronaviruse/situation-reports/20200121-sitrep-1-2019-ncov.pdf, [Accessed on 30 August 2020].• Wang C, Pan R, Wan X, Tan Y, Xu L, Ho CS, Ho RC. Immediate Psychological Responses and Associated Factors during the Initial Stage of the 2019 Coronavirus Disease (COVID-19) Epidemic among the General Population in China. Int J Environ Res Public Health. 2020 Mar 6;17(5):1729. https://doi.org/10.3390/ijerph17051729.• World Health Organization, WHO Director-General's opening remarks at the media briefing on COVID-19 - 11 March 2020. Available from: https://www.who.int/dg/speeches/detail/who-director-general-s-opening-remarks-at-the-media-briefing-on-covid-19---11-march-2020 [Accessed on 13 April 2020]• Coronavirus in India: Latest Map and Case Count. Available from: https://www.covid19india.org/ [Accessed 13 April 2020].• Arakal RA. First COVID-19 case in Karnataka: Techie who returned to Bengaluru from US tests positive, (9 March2020). Available from: https://indianexpress.com/article/cities/bangalore/coronavirus-karnataka-first-case-covid-19-bengaluru-6307223/ [Accessed on 13 April 2020]• India Today on 24 March 2020. Modi announces lockdown Updates: No panic buying please. Stay indoors, tweets PM. Available from: https://www.indiatoday.in/india/story/pm-modi-address-the-nation-at-8-pm-today-speech-covid-19-coronavirus-live-updates-1659215-2020-03-24 [Accessed on 13 April 2020]• Ali Jadoo SA. Was the world ready to face a crisis like COVID-19? Journal of Ideas in Health2020;3(1):123-4. https://doi.org/10.47108/jidhealth.Vol3.Iss1.45• Steptoe A, Shankar A, Demakakos P, Wardle J. Social isolation, loneliness, and all-cause mortality in older men and women. Proc Natl Acad Sci U S A. 2013;110(15):5797-5801. https://doi.org/10.1073/pnas.1219686110• Cao W, Fang Z, Hou G, Han M, Xu X, Dong J, et al. The psychological impact of the COVID-19 epidemic on college students in China. Psychiatry Res. 2020; 287:112934. https://doi.org/10.1016/j.psychres.2020.112934• Taylor HO, Taylor RJ, Nguyen AW, Chatters L. Social Isolation, Depression, and Psychological Distress Among Older Adults. Journal of Aging and Health2018; 30(2): 229–246. https://doi.org/10.1177/0898264316673511• Sim K, Huak Chan Y, Chong PN, Chua HC, Wen Soon S. Psychosocial and coping responses within the community health care setting towards a national outbreak of an infectious disease. J Psychosom Res. 2010;68(2):195-202. https://doi.org/10.1016/j.jpsychores.2009.04.004• Roy D, Tripathy S, Kar SK, Sharma N, Verma SK, Kaushal V. Study of knowledge, attitude, anxiety & perceived mental healthcare need in Indian population during COVID-19 pandemic. Asian J Psychiatr. 2020; 51:102083. https://doi.org/10.1016/j.ajp.2020.102083.• Karnataka Population. Available from: http://www.populationu.com/in/karnataka-population [Accessed on 8 April 2020]• Sample Size Calculator: Understanding Sample Sizes. Available from: https://www.surveymonkey.com/mp/sample-size-calculator/ [Accessed on 5 March 2020]• Toussaint A, Hüsing P, Gumz A, Wingenfeld K, Härter M, Schramm E, Löwe B. Sensitivity to change and minimal clinically important difference of the 7-item generalized anxiety disorder questionnaire (GAD-7). J Affect Disord. 2020; 265:395–401. https://doi.org/10.1016/j.jad.2020.01.032• Williams N. The GAD-7 Questionnaire [Review of the test Generalized anxiety disorder (gad-7) Questionnaire, by R. L. Spitzer]. Occupational Medicine2014; 64(3): 224. https://doi.org/10.1093/occmed/kqt161• Kroenke K, Spitzer RL, Williams JB. The PHQ-9: validity of a brief depression severity measure. J Gen Intern Med. 2001;16(9):606–613. https://doi.org/10.1046/j.1525-1497.2001.016009606.• Albert PR. Why is depression more prevalent in women? J Psychiatry Neurosci. 2015;40(4):219-221. https://doi.org/10.1503/jpn.150205• Patten SB, Wang JL, Williams JV, Wang JL, McDonald K, Bulloch ACM. Descriptive epidemiology of major depression in Canada. Can J Psychiatry. 2006; 51:84–90. https://doi.org/10.1177/070674371506000106• Jones C. Student anxiety, depression increasing during school closures, survey finds. EdSorce, 13 May 2020. Available from: https://edsource.org/2020/student-anxiety-depression-increasing-during-school-closures-survey-finds/631224 [Accessed on 29 August 2020].• Frasquilho D, Matos MG, Salonna F, Guerreiro D, Storti CC, Gaspar T, Caldas-de-Almeida JM. Mental health outcomes in times of economic recession: a systematic literature review. BMC Public Health2015; 16:115. https://doi.org/10.1186/s12889-016-2720-y.• Ali Jadoo SA. COVID -19 pandemic is a worldwide typical Biopsychosocial crisis. Journal of Ideas in Health2020;3(2):152-4. https://doi.org/10.47108/jidhealth.Vol3.Iss2.58• Prabhu N. Bengaluru urban tops state in per capita income, Kalaburagi last, (20 March 2016). Available from: https://www.thehindu.com/news/cities/bangalore/bengaluru-urban-tops-state-in-per-capita-income-kalaburagi-last/article8376124.ece [Accessed 13 April 2020].
Keywords: COVID-19, Pandemic, Social Isolation, Depression, Anxiety, Karnataka, India